STUDY OF FLEXIBLE PAVEMENT STRUCTURE MAINTENANCE IN RUNWAYS WITH PAVEMENT CONDITION INDEX (PCI) METHOD - Rachman, Meilinda Atika; Rahman, Harmein; Subagio, Bambang Sugeng; Hendarto, Sri (Jurnal Teknik Sipil, 2020)
AbstractRunway is an area in an airport for aircrafts to land and take off. The maintenance of the facilities on both the airside and landside must be taken care of in order to maximize the performance of the airport. Based on the aircraft type service plan of Balikpapan Sultan Aji Muhammad Sulaiman Sepinggan Airport and to maximize the performance of airports at present and in the future, an assessment of the condition of the runway with a Pavement Condition Index (PCI) value parameter on the flexible pavement to obtain the optimal repair or maintenance needs was carried out. The PCI obtained in 2019 was 61 (fair). Based on the PCI value in the runway, an evaluation was conducted with COMFAA and FAARFIELD to obtain the most critical aircraft PCN value in 2019. Segment 1, which is assumed to be half of the runway length which is sta 0 + 000 to 1 + 250, has a PCN value of 34.3 and segment 2, assumed to be of sta 1 + 250 - 2 + 500, has a PCN value of 33.2 where the ACN value for critical aircraft B777 - 300 ER is 89.3. In accordance with the recommendation of FAA AC-5380-6C, the most optimal scenario is scenario 2, which is major rehabilitation with the handling type of inlay - scrape and fill every 7 years when the PCI value is 49 (poor) and in the following years, routine maintenance would be done with patching. The total handling fee for 20 years of maintenance with scenario 2 is Rp. 195,377,000,000.  AbstrakRunway merupakan area pada bandar udara untuk tempat mendarat dan lepas landas bagi pesawat. Fasilitas ? fasilitas sisi udara dan sisi darat harus diperhatikan pemeliharaannya agar dapat memaksimalkan kinerja bandar udara. Berdasarkan rencana pelayanan tipe pesawat Bandar Udara Sultan Aji Muhammad Sulaiman Sepinggan Balikpapan dan untuk memaksimalkan kinerja bandar udara pada masa sekarang maupun pada masa yang akan datang, maka dilakukan penilaian kondisi perkerasaan runway dengan parameter nilai Pavement Condition Index (PCI) pada perkerasan lentur untuk mendapatkan kebutuhan perbaikan atau pemeliharaan yang optimal. Nilai PCI yang diperoleh pada tahun 2019 adalah sebesar 61 (fair). Berdasarkan nilai PCI pada runway tersebut dilakukan evaluasi dengan COMFAA dan FAARFIELD untuk mendapatkan nilai PCN pesawat terkritis pada tahun 2019. Pada segmen 1 yang diasumsikan setengah dari panjang runway yaitu sta 0+000 sampai 1+250 memiliki nilai PCN 34,3 dan segmen 2 diasumsikan dari sta 1+250 ? 2+500 memiliki nilai PCN 33,2 dimana nilai ACN untuk pesawat kritis B777 ? 300 ER adalah 89,3. Sesuai dengan rekomendasi FAA AC-5380-6C Skenario yang paling optimal adalah skenario 2  yaitu rehabilitasi mayor dengan jenis penanganan pengupasan dan pengisian perkerasan pada surface (inlay ? scrape and fill) setiap 7 tahun sekali ketika nilai PCI sebesar 49 (poor) dan pada tahun ? tahun berikutnya dilakukan pemeliharaan rutin dengan patching. Total biaya penanganan selama 20 tahun masa pemeliharaan dengan skenario 2 sebesar Rp. 195.377.000.000.